Designing IoT based posture monitoring system - Ramalingam, Mritha; Puviarasi, R.; Shern, Quah Chia; Chinnavan, Elanchezhian (Institute of Electrical and Electronics Engineers Inc., 2021)
With the existence of vast increase in the usage of digital equipment such as computers and other smart devices in their work, people tend to face several health issues. This utilization of digital technology makes people spend most of their time by sitting in one place for a long time. This results in creating several illnesses to them. People do not realize their sitting posture which might hurt their body over a long run of inappropriate sitting practice. As a result, this paper aims to design a system to monitor the posture of the neck and body of a person in sitting position. This proposal utilizes the Internet of Things (IoT) such as microcontroller, sensor, etc., to monitor the body posture of a person and help people to correct their body posture.